Compensation Decisions on Disruption Recovery Service in Urban Rail Transit - Yang, Zhijie; Chen, Xiaolong (Promet - Traffic&Transportation, 2019)
Ride-hailing, in addition to a common mode of daily transportation, is an attractive option for evacuating stranded passengers and supplementing bus bridging in the early stages of an urban rail transit (URT) disruption. This paper proposes a service supply chain comprised of ride-hailing vehicles, ride-hailing platforms, and stranded passengers wherein the URT and ride-hailing chain together provide emergency evacuation services. The emergency evacuation service supply chain can be coordinated under an effort-based revenue sharing contract. A URT-dominated Stackelberg game model between the URT and ride-hailing platform is then formulated to optimize compensation decisions on the part of the URT; numerical analysis reveals critical factors affecting the said decisions. The main contributions of this paper are two-fold: first, it provides new information regarding collaboration between URT operators and ride-hailing platforms for stranded passenger evacuation, including a ride-hailing platform pricing strategy; and second, the URT compensation decision process is solved via Stackelberg game model while revealing an incentive coefficient parameter for the URT decision and solver.